Antioxidant Activity of 96% Ethanol Extract of Pepaya Jepang Leaves (Cnidoscolus aconitifolius (Mill.) I. M. Johnst) Using DPPH Method (1,1-diphenyl-2-picrylhydrazyl) - Riskianto Riskianto; Melieta Windi; Karnelasatri Karnelasatri; Maroloan Aruan (Borneo Journal of Pharmacy, 2022)
Free radicals in the human body can be helped neutralized by natural antioxidants derived from plants. Pepaya Jepang (Cnidoscolus aconitifolius (Mill.) I.M.Johnst) contains antioxidant compounds such as flavonoids and polyphenols. This study examined the antioxidant activity of 96% ethanol extract of C. aconitifolius leaves. Maceration of C. aconitifolius leaves using 96% ethanol solvent, phytochemical screening, and antioxidant activity assay was carried out with 1,1-Diphenyl-2-Picryl Hydrazil (DPPH) on 96% ethanol extract of C. aconitifolius. Extraction obtained a yield of 16.1834%, and phytochemical screening on the 96% ethanol extract of C. aconitifolius contained flavonoids, tannins, saponins, phenols, alkaloids, and steroids. The antioxidant activity assay on 96% ethanol extract of C. aconitifolius had an IC50 value of 145.3855 ppm and an IC50 value of vitamin C of 7.0806 ppm. The Antioxidant Activity Index (AAI) of 96% ethanol extract of C. aconitifolius was 0.4127, and the AAI of vitamin C was 8.4739. Based on the results obtained, although in a weak classification, a 96% ethanol extract of C. aconitifolius leaves has antioxidant activity.